e-Site Analysis: Process Design of Site Utility Systems With Electrification for Process Industries - Kim, Jin-Kuk (Frontiers in Thermal Engineering, 2022)
A new design methodology for the process synthesis of electrified energy systems, e-site analysis, for the application of process industries, is presented, which allows the systematic selection of electrified units in process levels and provides design guidelines for the configuration of site utility systems. Different characteristics associated with the use of power-to-heat technologies for thermal heating, compared with traditional heat supply from the combustion of fossil fuels, are discussed in the context of process design and site-wide utility management. The new design framework is developed for the transformation of conventional steam-based utility systems to electricity-based ones. The applicability of the proposed design method and its benefits from carbon-neutral energy generation is demonstrated with a case study, which clearly illustrates the impact of electrification on the design and operation of site utility systems in process industries.